2009
DOI: 10.1177/1367493509344824
|View full text |Cite
|
Sign up to set email alerts
|

‘They wouldn’t know how it feels . . .’: characteristics of quality care from young people’s perspectives: a participatory research project

Abstract: Literature suggests there is a need to hear from children themselves about the quality of healthcare they receive and, although their views are increasingly sought, little is known about children’s definitions of ‘high or low quality care’. This article reports on a participatory, qualitative study that set out to explore with children and young people whether they could be involved in monitoring the quality of hospital care. Nine young people played an active role in the research process, collecting data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…For outpatient facilities, our findings correspond with those of other studies that also indicated the importance of good explanations and having a choice,33 as well as of more efficient services and reduced waiting times 27,47. A study by Wray and Maynard also demonstrated that both streamlined care processes in the outpatient department and care interactions are important to young people with congenital heart conditions who move to adult services 47.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For outpatient facilities, our findings correspond with those of other studies that also indicated the importance of good explanations and having a choice,33 as well as of more efficient services and reduced waiting times 27,47. A study by Wray and Maynard also demonstrated that both streamlined care processes in the outpatient department and care interactions are important to young people with congenital heart conditions who move to adult services 47.…”
Section: Discussionsupporting
confidence: 89%
“…Honesty, respect, a caring and friendly attitude, being focused on adolescents, and technical competence are all important 9,23,26,33,46. Trustworthiness seems a core attribute for professionals and is related to good communication skills and respect for teenagers’ opinions and privacy 20,25,31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children and consumers’ views were not sought during this initial process of identifying quality indicators. Quality indicators would be enhanced if input was sought from children and families as consumers and community members (McKenzie & Hanley 2007, Moules 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Where it may be difficult and ethically inappropriate to follow up data collection at certain times. Albeit other issues such as children's intensive care experiences and palliative and end of life care have been investigated and the challenges addressed (Bellali et al 2007, Moules 2009, Grinyer 2012. However, in addition there are perhaps challenges of the social judgements that research into parenting might evoke.…”
Section: Childhoods Living With Illnessmentioning
confidence: 99%